Building on Early Gains in Afghanistan's Health, Nutrition, and Population Sector : Challenges and Options. - Belay, Tekabe (World Bank Publications, 2010)
Afghanistan has made considerable progress since 2001. A nationwide survey conducted in late 2006 found that the IMR had fallen to 129 per 1,000 live births, and the U5MR had fallen to191 per 1,000 live births, representing a 22 percent and 26 percent decline, respectively, from the end of 2001. Similarly, prenatal care coverage has increased from less than 5 percent to 32 percent, and DTP3 coverage has increased from less than 20 percent to 35 percent between 2003 and 2006. Administrative data indicate that the number of functioning primary health care facilities has nearly doubled from 498 i.